2023
DOI: 10.1002/biot.202200440
|View full text |Cite
|
Sign up to set email alerts
|

Liamocin biosynthesis is induced by an autogenous host acid activation in Aureobasidium melanogenum

Mei Zhang,
Xin Wei,
Peng Wang
et al.

Abstract: It has been known that maximal liamocin production must be carried out at low environmental pH (around 3.0). In this study, it was found that the low pH was mainly caused by the secreted citric acid which is one precursor of acetyl‐CoA for liamocin biosynthesis. Determination of citric acid in the culture, deletion, complementation and overexpression of the CEXA gene encoding specific citrate exporter demonstrated that the low pH was indeed caused by the secreted citric acid. Deletion, complementation and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Under such acid conditions (pH 3.0), the autogenous host acid activates the transcriptional activator PacC with three‐zinc fingers (Cys 2 His 2 ) in the pH signaling pathway, indicating that the PACC gene encoding the transcriptional factor in the pH signaling pathway was an acid‐expressed gene in A. melanogenum . [ 15 ] We also found that the low pH (3.0) adjusted with HCl has positive influence on liamocin production. [ 15 ] It was discovered that overexpression the PK gene for phosphoketolase, the PDC gene encoding pyruvate decarboxylase and VHb gene coding for Vitreoscilla hemoglobin (VHb) in the glucose de‐repression mutants can make the engineered strain V33 produce 55.38 g L −1 of liamocin within 168 h during the 10‐L fermentation [ 17 ] while its wild type strain 9‐1 only produce 30.61 g L −1 of liamocin from 117.60 g L −1 of glucose within 168 h of the same fermentation.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Under such acid conditions (pH 3.0), the autogenous host acid activates the transcriptional activator PacC with three‐zinc fingers (Cys 2 His 2 ) in the pH signaling pathway, indicating that the PACC gene encoding the transcriptional factor in the pH signaling pathway was an acid‐expressed gene in A. melanogenum . [ 15 ] We also found that the low pH (3.0) adjusted with HCl has positive influence on liamocin production. [ 15 ] It was discovered that overexpression the PK gene for phosphoketolase, the PDC gene encoding pyruvate decarboxylase and VHb gene coding for Vitreoscilla hemoglobin (VHb) in the glucose de‐repression mutants can make the engineered strain V33 produce 55.38 g L −1 of liamocin within 168 h during the 10‐L fermentation [ 17 ] while its wild type strain 9‐1 only produce 30.61 g L −1 of liamocin from 117.60 g L −1 of glucose within 168 h of the same fermentation.…”
Section: Introductionmentioning
confidence: 73%
“…[ 15 ] We also found that the low pH (3.0) adjusted with HCl has positive influence on liamocin production. [ 15 ] It was discovered that overexpression the PK gene for phosphoketolase, the PDC gene encoding pyruvate decarboxylase and VHb gene coding for Vitreoscilla hemoglobin (VHb) in the glucose de‐repression mutants can make the engineered strain V33 produce 55.38 g L −1 of liamocin within 168 h during the 10‐L fermentation [ 17 ] while its wild type strain 9‐1 only produce 30.61 g L −1 of liamocin from 117.60 g L −1 of glucose within 168 h of the same fermentation. [ 17 ]…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations